2020
DOI: 10.1088/1361-6528/ab6fdc
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal boron nitrides reduce the oxidative stress on cells

Abstract: The molecular stress caused by a drug administered to treat a disorder on healthy cells appears as a side effect. In this study, we aim to understand the potential of hexagonal boron nitrides (hBNs) as a therapeutic agent to relieve the cellular stress exerted by drugs. First, the cytotoxicity of hBNs and their possible degradation product, boric acid (BA), on the embryonic mouse hippocampal cell line mHippo E-14 was assessed in a wide concentration range (4.4-440 μg ml −1 ) of boron including hBNs and BA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two-dimensional hexagonal boron nitride (h-BN) connected by strong sp 2 covalent bonding, an isomorph of graphene with similar lattice parameters [ 98 ], is receiving great attention in future electronic devices due to excellent mechanical properties [ 99 , 100 ], chemical stability [ 101 , 102 ] and optical properties [ 103 ]. Similar to other 2D materials, the layered structure bulk h-BN can be separated into monolayer or 2D structures with a thickness of several nanometers by mechanical and chemical exfoliation [ 104 117 ].…”
Section: Types Of 2d Materials Applicable For Remote Epitaxymentioning
confidence: 99%
“…Two-dimensional hexagonal boron nitride (h-BN) connected by strong sp 2 covalent bonding, an isomorph of graphene with similar lattice parameters [ 98 ], is receiving great attention in future electronic devices due to excellent mechanical properties [ 99 , 100 ], chemical stability [ 101 , 102 ] and optical properties [ 103 ]. Similar to other 2D materials, the layered structure bulk h-BN can be separated into monolayer or 2D structures with a thickness of several nanometers by mechanical and chemical exfoliation [ 104 117 ].…”
Section: Types Of 2d Materials Applicable For Remote Epitaxymentioning
confidence: 99%
“…Similarly, Taskin et al showed that the round-shaped BNs they used in their studies did not generate ROS at low doses. 21 Also a recent study on hBN particle with round shape showed that hBNs led to increases of TAS levels and decreases of TOS levels in Parkinson Disease model. 5 In this case, the reliability of the medical grade hBN may be related to the morphological structure.…”
Section: Discussionmentioning
confidence: 97%
“…Based on previous work on the preparation of 10 B-enriched boron nanoparticles for treating murine brain tumors via BNCT, we used the ALTS1C1 cells as a model study for a proof-of-concept demonstration [43]. Although it is well known that nanoparticle drugs cannot infiltrate the blood-brain barrier (BBB) to treat brain-related diseases, researchers have used various strategies to temporarily disrupt the BBB to allow nanotherapeutics to be delivered to the brain [92,93]. Moreover, research has demonstrated that the ALTSIC1 murine brain tumor model is highly infiltrative, making it a suitable candidate for future in vivo studies [91].…”
Section: Cytotoxicity Study Of the Bcno Pei@bcno And Peg@bcnomentioning
confidence: 99%